Evaluating the Impact of Prescribed Versus Nonprescribed Benzodiazepine Use in Methadone Maintenance Therapy: Results From a Population-based Retrospective Cohort Study. Issue 3 (May 2019) - Eibl, Joseph K.; Wilton, Andrew S.; Franklyn, Alexandra M.; Kurdyak, Paul; Marsh, David C.
Abstract : Objectives: Benzodiazepine (BZD) use is common in patients who are engaged in methadone as a treatment for opioid use disorder. BZD prescribing is generally discouraged for this patient population due to the increased risk of BZD dependence and BZD use disorder, medication-assisted treatment (MAT) discontinuation, and opioid-overdose death. However, some patients have concurrent mental health disorders, where BZD use may be clinically indicated. This study evaluates the impact of prescribed BZD on MAT outcomes. Methods: Linking urine drug screening data (UDS) and prescribing information from single-payer health records, we conducted a retrospective Kaplan–Meier analysis between patients using prescribed and nonprescribed BZD with methadone treatment retention as the primary outcome. Data are from a network of 52 outpatient clinics in Ontario, Canada, between January 1, 2006 and June 30, 2013. Results: We identified 3692 patients initiating methadone-assisted treatment for the first time; 76% were BZD−/UDS− (no BZD prescription and <30% screens positive for BZD); 13% were BZD+/UDS−; 6% BZD−/UDS+; and 6% BZD+/UDS+. Using 1-year treatment retention as a primary outcome, patients using nonprescribed BZD (BZD−/UDS+) were twice as likely (adjusted odds ratio 0.38, 95% confidence interval 0.27–0.53) to discontinue treatment as those not using BZD (BZD−/UDS−), or those using BZD in a prescribed manner (BZD+/UDS+). Conclusions: Our findings suggest that prescribed BZD can be used during methadone MAT without impacting a patient's retention in MAT, but nonprescribed BZD use is predictive of treatment discontinuation. Importantly, we urge both the physician and patient to seek alternative clinical options to BZD prescribing, due to the potential for developing physical dependence (and BZD use disorder) to BZD and the risks of negative interactions with opioids.